(untitled) (European Journal of Pure and Applied Mathematics, 2013)
In this paper a new kind of sets called generalized closed sets are introduced and studied in a topological space by using the concept of operation in a topological space.Â Some of their properties are investigated. Finally, some characterizations of ψ_g-regular, ψ_g-normal spaces are given.